MOMENTS AND THEIR MEN: METAPHOR AND ANALOGY IN FACEWORK (Theoretical and Applied Linguistics@ro, 2025)
Offences have negative effects on the public image of the offended party and on the expressive order of the verbal exchange in which they occur. Taking the Goffmanian interchange as a model, the article analyses several interactions in which participants process a possible offence with the help of a particular device consisting of source analogues, in order to neutralize these effects. Participants first map the first source (metaphor) to check whether it correctly identifies the pragmatic value of the offence. Then, they map the second source (analogy) to jointly discover the target configuration. The target – the specific conversational situation in which the offence occurred, along with the resulting balance of power between the interlocutors – is treated as unknown or less well-known than the source. The target is protean and mobile, and may draw in or remove past elements of the ongoing conversation.The participants in the verbal interactions analysed have a high degree of reflexive awareness, as evidenced by the fact that they propose and reject ideas, formulate new proposals, develop them, and ultimately agree on the pragmatic value to be attributed to a particular utterance that is perceived as potentially offensive. The type of moment we are concerned with in this study does not have the disadvantages of excuses, which impose a burden on both the person asking and the person receiving. With this device, participants can effectively negotiate the meaning of an utterance. It also has the ability to build and develop social relations between participants. Mapping the correspondences between the source and the target reveals that there are reciprocal relations between the participants – they are together in the analogy scenario and the differences between the offender and the offended disappear.
Keywords: facework; metaphor; analogy; podcasts